High throughput screening of the potential biosurfactants production by extremophiles isolated from vinasse and black liquor - Rivero, Mariano (2023)
The aims of this work were to isolate microorganisms from vinasse (V) and black liquor (BL), by-products of alcohol and paper industries and to assess their potential as substrates to produce biosurfactants. Thirty-nine microorganisms, 19 from V (acidophilic, a1 to a19) and 20 from BL (alkaliphilic, b1 to b20) were isolated. A high- throughput method was design and set up for surface tension (γ) measurement. In the first screening, 15/39 strains were pre-selected for their capacity of γ reduction of media formulated with V and BL. A Student's t-test was applied to data obtained in the second screening, to search for significant differences among γ values reached in each production media and their respective sterile medium. Three acidophilic (a1, a5, a6) and 3 alkaliphilic (b1, b2, b17) significantly decreased the γ compared to the control (p < 0.05) after 5 days with 5% of substrate concentration. A BCindex was defined to assess biosurfactant capacity. The strains showed the following percentage of γ reduction: Lactobacillus rhamnosus a5 (34%), Bacillus safensis b1 (13%), Alkalihalobacillus halodurans b2 (10%) and Pichia cecembensis a6 (10%), Lactobacillus paracasei a1 (6%). The two strains that presented the best potential biosurfactant capacity and the greatest γ reduction when compared to the control (p-value) were Lactobacillus rhamnosus a5 (BCindex = 16.98, p = 0.007), and Bacillus safensis b1 (BCindex = 17.66, p = 0.003). These industrial by-products are a source of new super-producing strains and will be assess as economic substrates for biosurfactant production.